SHORT COMMUNICATION: PREVIOUSLY UNREPORTED HUMAN−PRIMATE CONFLICT IN KALISALAK FOREST, CENTRAL JAVA-INDONESIA - Nasution, Erie; Al Hakim, Rosyid; Aoliya, Nur (Lembaga Pengembangan Kinerja Dosen, 2022)
We found the phenomenon of human−primate conflict (HPC) in the Kalisalak Forest, Central Java, Indonesia. This location is also known locally as the research site of the Kalisalak Study Site or Kalisalak Grand Forest Park (KGFP) and is used for religious activities by local ethnicities. The research site is used for pilgrimages every Suro Month in the Islamic calendar. Based on the history adopted from the local people, the macaques already existed in the colonial period of the Dutch East Indies. We interviewed